Training an implicit reasoning strategy: engaging specific reasoning processes to enhance knowledge acquisition - Vowels, Christopher L. (Kansas State University, 2008)
A training protocol was developed to teach an implicit reasoning strategy to encourage the consideration of alternatives, specifically in behavioral trap decision environments. Engaging the strategy would thereby decrease the effect of focusing on traps, resulting in more rational behavior. In two studies, training was delivered in an instructor-less environment using paper-pencil and multimedia examples. The main training components consisted of analogical problem solving and counterfactual thinking. The potential moderators between training and performance outcomes consisted of an information processing disposition Need for Cognitive Closure, an individualized approach to decisions, Decision-Making Style, and a capacity to process information Working Memory Capacity. Arousal and mood were also measured before, during, and after the training as both have been linked with learning. In Study 1, participants engaged in analogical problem solving, additive counterfactual thinking, subtractive counterfactual thinking, or none of these (i.e., control group). Results revealed that the training was minimally effective, although some comparisons revealed a large shift from pre- to post-training in commitment score away from trap options. Likewise, the Need for Cognitive Closure was the best predictor of decision behavior revealing that a predisposition for amount of information processed during decision making is indicative of behavioral outcomes in this decision environment. Based on results from Study 1, the training was reformatted in Study 2 to obtain the maximum potential benefit. Analogical problem solving was coupled with each form of counterfactual thinking so participants engaged in both critical thinking processes. When training was effective, the two forms were differentially effective as related to behavioral trap problem type. Forward-looking training assisted problem types that force explicit cost recognition and immediate decision outcomes. Past-looking training assisted problem types that force little cost recognition and delayed decision outcomes. Results of this project could be used to enhance the acquisition of critical thinking as well as improve educational practices. Both information processing disposition and decision approach style predicted learning whereas capacity to process information and training manipulations did not. Future projects will examine how long the training effects last and if critical thinking training can be successfully applied to other decision environments.
Keywords: Decision-making; Implicit Learning; Training; Analogical Problem Solving; Counterfactual Thinking; Working Memory Capacity; Psychology, Experimental (0623)